Opportunity and Place: Latino Children and America's Future. Issue 1 (July 2021) - Lichter, Daniel T.; Johnson, Kenneth M.
We examine the spatial distribution of Hispanic children and analyze its relationship to the geography of opportunity. We describe the spatial distribution of Hispanic children across all U.S. counties, document their exposure to salutary and deleterious conditions, and compare exposure to these conditions among children living in metropolitan and nonmetropolitan counties that represent traditional and new destinations for immigrants. We find clear evidence of racial and geographic differences in opportunity, at least as defined by spatially uneven patterns of intergenerational mobility. We show that the typical Hispanic child is highly isolated, living in a county with a majority-minority population, high rates of poverty, low levels of education, and poor public health. Opportunities are limited in metropolitan core counties, where the large majority of Hispanic children live, and the movement of immigrant families from traditional gateways to new destinations provides little to children in terms of exposure to more opportunity.